2020
DOI: 10.13004/kjnt.2020.16.e10
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Thecal Sac Compression Induced by Hydrogel Dural Sealant after Spinal Schwannoma Removal

Abstract: Cerebrospinal fluid (CSF) leak is a common complication of spinal and cranial surgery, and patients undergoing spinal tumor surgery are probably particularly predisposed due to the presence of an intradural tumor and many other factors. Furthermore, a meticulous dural closure technique does not always result in watertight closure. A number of adjunctive methods have been used to assist with dural closure. Synthetic, absorbable polyethylene glycol hydrogel dural sealants are widely used and have been approved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…One main disadvantage is the extensive swelling behaviors of PEG‐based hydrogels, which can significantly deteriorate its mechanical properties and limit its uses in circumstances that are sensitive to the hydrogel shape and volume, such as in potential neural compression by a spinal sealant. [ 445 ] Efforts have been made to achieve nonswellable hydrogels by introducing thermosensitive moieties into the backbone ( Figure ), [ 31,118,446 ] or more generally, by controlling the polymer–solvent interaction parameter (χ), [ 447 ] but how these will affect their tissue adhesion remains to be determined. In a recent study, Hayashi and colleagues demonstrated such low swellable PEG hydrogels to be useful for the application as artificial vitreous bodies.…”
Section: Polymer Precursorsmentioning
confidence: 99%
“…One main disadvantage is the extensive swelling behaviors of PEG‐based hydrogels, which can significantly deteriorate its mechanical properties and limit its uses in circumstances that are sensitive to the hydrogel shape and volume, such as in potential neural compression by a spinal sealant. [ 445 ] Efforts have been made to achieve nonswellable hydrogels by introducing thermosensitive moieties into the backbone ( Figure ), [ 31,118,446 ] or more generally, by controlling the polymer–solvent interaction parameter (χ), [ 447 ] but how these will affect their tissue adhesion remains to be determined. In a recent study, Hayashi and colleagues demonstrated such low swellable PEG hydrogels to be useful for the application as artificial vitreous bodies.…”
Section: Polymer Precursorsmentioning
confidence: 99%
“…The reduced swelling rate of the bi‐layer patch may be due to the addition of MBG and the extension of the exposure time when printing the first layer of patch. The swelling rate of the bi‐layer patch was lower than that of DuraSeal (50%), [ 53 ] and the grid structure did not deform after swelling (Figure S3E, Supporting Information). According to previous research, [ 54 ] the incorporation of MBG nanoparticles reduces the degradation rate of hydrogels due to the enhanced cross‐linking of MBG.…”
Section: Resultsmentioning
confidence: 99%
“…The healing pe-riod of surgical areas such as muscles, skin, and bones may be prolonged due to CSF leakage. This can potentially lead to complications such as meningitis, nausea, vomiting, vertigo, tinnitus, postural headache, and fistula formation 3,5,13) . Therefore, preventing CSF leakage is very important.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) leakage is a rare complication that can occur in spinal surgery. Postoperative CSF leakage can induce delayed healing, wound infections, and intracranial hypotension, which causes neurological symptoms such as postural headache, vomiting, and dizziness 3,5,[11][12][13] . Repair of CSF leakage due to dural defects that may occur during surgery is very important and Dural Sealant System can be used in this case.…”
Section: Introductionmentioning
confidence: 99%